Speak up skills of oral communication [videorecording] - Center for Humanities (Mount Kisko, N.Y. Makati The Center Felta Book Sales [distributor], 1977)
Explores how subject, audience and purpose affect oral communication, influencing not only what is said. Presents dramatization of ineffective communication and explains how each could have been avoided. It gives an in depth discussion on public speaking as the main focus of oral communication. It defines the elements of speech and points out what makes a good one.
VHS.
Keywords: Oral communication; Communication